ANALISIS BAGI HASIL PENDAPATAN USAHA TANI KARET DI KELURAHAN RAWANG EMPAT KECAMATAN BANDAR PETALANGAN KABUPATEN PELALAWAN - Sukiadi Indra; Setiawan Deny; Taryono Taryono (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2020)
This study aimed to discuss the system of the split income of rubber farming, the income level of rubber tappers and the income of landowners in Rawang Empat, Bandar Petalangan, Pelalawan. The population of this study was 57 people who did the split income system, used the census sample as sampling method that all people who carried out the system are categorized as the sample. The data were primary data and secondary data. The data were collected by using interview techniques, questionnaire, and documentation. The analytical method used in this research was descriptive and quantitative using Revenue formulas. The results of this study show the system of split income in Rawang Empat, Bandar Petalangan, Pelalawan. There are two split income systems found in this study, the first is ½ split income (equal share between the landowners and tapping farmers) and the second is 1/3 split income (1 for landowner and 2 for tapper farmers), with details of the cost of dependents by each party is different. Based on the split income between the landowners and tapping farmers, it can be concluded that the size of the income of tapping farmers and landowners is in accordance with the magnitude of the responsibilities of each party. Dependents issued by land owners are greater than tappers' dependents, so that the income of tapping farmers is greater than the income of landowners in Rawang Empat, Bandar Petalangan, Pelalawan.Keywords: Split Income System, Rubber Farmer Income.